The (De)Legitimization of Violence in Sacred and Human Contexts - Shafiq, Muhammad; Donlin-Smith, Thomas (Springer International Publishing, 2021)
1: Introduction -- 2: Violence and The Cross: The Affinity Between Theories of Atonement and Christian Attitudes Towards War and Peace -- 3: Facing Down Fear: John Chrysostom’s Answer to Violence -- 4: The Parable of the Wedding Protest: Matthew 22:1-14 and Nonviolent Resistance -- 5: Refuting the Violent Image of God in the Book of Joshua 6-12 -- 6: The Conflict of War: Unresolved Challenges and Sentiments in Jewish Sources -- 7: Remodeling the Paradigm of Religious Inference and Decision Making in Islam: Converting Dogmatism into a Positive and Vibrant Human Activity -- 8: Violence or its De-Legitimization? Conflicting Views from the Hindu World -- 9: Speak Dhamma but Carry a Big Stick: Violence in Early Buddhist Discourse -- 10: War and Religious Discourse in the Russia-Ukraine Conflict -- 11: The Quest for Radical Islamism and the War on Terror in Indonesia -- 12: The Violent Wahhabism and the Use of Islamic Texts to Justify Armed Violence Against Muslims and Non-Muslims -- 13: Embracing Nonviolence: Pope Francis and Catholic Teaching on War -- 14 Covert Violence: Counting Cultural Trauma at the Intersection of ATR, Islam and Neoliberalism in Africa -- 15: The Myth of Islam as Inherently Violent -- 16: “Heads Will Roll:” Decapitations in Mughal Painting – Persecution or Punishment? -- 17: Islamophobia and the Far-Right in Modern Germany, 2008-2018: An Introduction -- Concluding Remarks.